2022
DOI: 10.3389/fimmu.2022.916645
|View full text |Cite
|
Sign up to set email alerts
|

Causal Association Between Inflammatory Bowel Disease and Psoriasis: A Two-Sample Bidirectional Mendelian Randomization Study

Abstract: BackgroundPrevious observational studies have found an association between inflammatory bowel disease (IBD) and psoriasis. Using the mendelian randomization (MR) approach, we aim to determine whether there was a causal association between IBD and psoriasis.MethodsWe performed a two-sample MR with the genetic instruments identified for IBD and its main subtypes, Crohn’s disease (CD) and ulcerative colitis (UC), from a genome-wide association study (GWAS) involving 25,042 cases with an IBD diagnosis and 34,915 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 43 publications
0
30
1
Order By: Relevance
“…To avoid this, we also used the MR approach. This approach, described as the "natural randomized controlled trial", is an alternative when randomized controlled trials are unethical or unfeasible and MR studies in medical science, including in the field of psoriasis (36)(37)(38)(39)(40)(41), are increasing (42,43). The present MR results are in agreement with a recent two-sample bidirectional MR study by Zhao et al, investigating causal directions of several comorbidities with psoriasis and psoriasis arthritis (44) without finding a causal association between NAFLD and psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid this, we also used the MR approach. This approach, described as the "natural randomized controlled trial", is an alternative when randomized controlled trials are unethical or unfeasible and MR studies in medical science, including in the field of psoriasis (36)(37)(38)(39)(40)(41), are increasing (42,43). The present MR results are in agreement with a recent two-sample bidirectional MR study by Zhao et al, investigating causal directions of several comorbidities with psoriasis and psoriasis arthritis (44) without finding a causal association between NAFLD and psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Since our results seem to be interesting in the literature there are a few studies which present similar results. Yajia et al have presented another MR analysis which confirms the bidirectional relationship between psoriasis, psoriatic arthritis, and CD 50 . However, findings of Dennis' study only support a unidirectional causal effect between CD and psoriasis as well as psoriatic arthritis 51 .…”
Section: Discussionmentioning
confidence: 81%
“…The MR study mimics the randomized controlled trial by using genetic variants as robust proxies for modifiable exposures (Figure 1). The use of MR studies in medical science is increasing (13, 36), also in the field of psoriasis (37)(38)(39)(40)(41)(42). Recently, two studies reported that smoking was a causal risk factor for psoriasis (38, 43), which we could not confirm.…”
Section: Discussionmentioning
confidence: 83%